Combining Geoelectrical Measurements and CO2 Analyses to Monitor the Enhanced Bioremediation of Hydrocarbon-Contaminated Soils: A Field Implementation. (17th February 2016) - Noel, Cécile; Gourry, Jean-Christophe; Deparis, Jacques; Blessing, Michaela; Ignatiadis, Ioannis; Guimbaud, Christophe
Abstract : Hydrocarbon-contaminated aquifers can be successfully remediated through enhanced biodegradation. However, in situ monitoring of the treatment by piezometers is expensive and invasive and might be insufficient as the information provided is restricted to vertical profiles at discrete locations. An alternative method was tested in order to improve the robustness of the monitoring. Geophysical methods, electrical resistivity (ER) and induced polarization (IP), were combined with gas analyses, CO2 concentration, and its carbon isotopic ratio, to develop a less invasive methodology for monitoring enhanced biodegradation of hydrocarbons. The field implementation of this monitoring methodology, which lasted from February 2014 until June 2015, was carried out at a BTEX-polluted site under aerobic biotreatment. Geophysical monitoring shows a more conductive and chargeable area which corresponds to the contaminated zone. In this area, high CO2 emissions have been measured with an isotopic signature demonstrating that the main source of CO2 on this site is the biodegradation of hydrocarbon fuels. Besides, the evolution of geochemical and geophysical data over a year seems to show the seasonal variation of bacterial activity. Combining geophysics with gas analyses is thus promising to provide a new methodology for in situ monitoring.